PEMBELAJARAN BERBICARA BERBASIS MASALAH: STRATEGI DAN PENDEKATAN SEBAGAI IMPLEMENTASI KURIKULUM 2013 - Setyonegoro, Agus (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2015)
The main goal of learning speaking is to build conversational skills of learners. Learning speaking is a learning process that aims to enable students to understand and apply the forms of act follow oral language-related aspects of intellectual, factual information, emotional attitude. The formulation of learning objectives speaking is in separable from effective aspects, cognitive, and motor. Curriculum 2013 with a scientific approach mandates that every part of learning should support the establishment of three competencies at the same time, the attitude, knowledge, and skills. This purpose can be achieved best when learning to talk hosted by the approach and the right strategy. The ability to speak the learners needed to be stimulated with the ability to demonstrate the skill of speaking. Student centered learning means the students are conditioned to dominate the activity of speaking. Scientific approach to problem-based learning to speak, emphasizing the activity of speaking learners to solve the problem posed by the teacher. Activity speaking learners are shown in each stages of the process of solving the problem, namely: 1) the stage of conveying an idea; 2) the stage of presentation of the known facts; 3) the stage of studying the learning issues; 4) the stage of the action plan; 5) evaluation. Keywords: learning, speaking, problem-based, strategy, approach, curriculum 2013